Kontribusi Istri Petani terhadap Pendapatan Rumah Tangga Petani di Desa Masalili Kecamatan Kontunaga Kabupaten Muna - Eva Aziza; Ilma Sarimustaqiyma Rianse; Samsul Alam Fyka (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This research aims to find out: (1) the husband's income as a farmer. (2) the income of the farmer's wife (3) the contribution of the farmer's wife to the income of the farmer's household in Masalili Village, Kontunaga District, Muna Regency. This research was carried out in Masalili Village, Kontunaga District, Muna Regency from January 2023 to July 2024. The data used were primary and secondary data. The analysis used in this research is presented in table form. The main commodities cultivated by farmers are corn, cassava and tapping palm sap. The average husband's income in the agricultural sector in Masalili Village, Kontunaga District, IDR 30,151,595/year, this value is obtained from the value of income minus the value of farming production costs. The average income of farmers' wives is IDR 14,413,228/year with an average income of IDR 19,048,200/year and average expenses of IDR 4,580,972/year. This income is obtained from the kamooru weaving business, with an average income of IDR 9,671,728/year and also additional income from businesses in the agricultural sector, namely as a farm laborer and also a vegetable seller, with an average income of IDR 4,792,500/year. The results of the analysis show that farmer wives contribute 31.87% to farmer household income, while husbands' income from the agricultural sector contributes 68.12% with an average total income of farmer households of IDR 45,386,866/year.